Pendidikan Islam dalam Sistem Pendidikan Nasional - Jannah, Fathul (Dinamika Ilmu, 2013)
Islamic educationis an integral part of the National Education System. As part of the national educational system, Islamic education gets legitimacy to exist and get a place to live and thrive in Indonesia to meet need of education for Muslims. Accommodation to the Islamic education system and make the system of Islamic education institutions have a strong foundation to be developed with the support of funds and attention from the state. Therefore, the state is obliged to develop Islamic educational system as a kind of religious education in the national education system. In the system of national education, Islamic education as a system of religious education is carried out in different lines of formal, informal and non-formal.